Прогнозирование трафика сети мобильной связи третьего поколения - Роздымаха, Е. А.; Омельченко, А. В.; Фёдоров, А. В. (ХНУРЭ, 2013)
Infocommunication networks development demands that prior network planning should be applied. This requires network traffic prediction that is necessary to make management decisions on efficient network resources utilization and subscribers servicing. It determines the actuality of constructing corresponding mathematical models, which use statistical data collected in the operation of a mobile network with the help of automated measuring systems. The analysis of the actual network traffic of third generation mobile communication network is done. The fractal (self-similar) properties of traffic are shown. The estimates of Hurst parameter of stochastic trend of actual traffic is obtained. It is shown that the considered mathematical model of network traffic can be used to solve the problems of prediction and planning of the mobile network. The estimates of dependence of the prediction quality on the prediction step is obtained.